2017
DOI: 10.22159/ijpps.2017v9i2.15853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solvent Polarity on Solvation Free Energy, Dipole Moment, Polarizability, Hyperpolarizability and Molecular Reactivity of Aspirin

Abstract: <p><strong>Objective: </strong>The aim of the study is to explore the effects of solvent polarity on solvation free energy, dipole moment, polarizability, first order hyperpolarizability and different molecular properties like chemical hardness and softness, chemical potential, electronegativity, electrophilicity index of aspirin which may lead to better understand the reactivity and stability of aspirin in different solvent systems.</p><p><strong>Methods: </strong>Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…It has been reported that differences in solvent polarity and the type of solute-solvent interaction(s) have an impact on the physicochemical properties of molecules, attributing to interactions with the transition state of individual molecules. Therefore, differences in the stability and reactivity as well as the molecular spectrum of the molecule is expected (23)(24)(25)(26).…”
Section: Methods Validation For Determination Of Asamentioning
confidence: 99%
“…It has been reported that differences in solvent polarity and the type of solute-solvent interaction(s) have an impact on the physicochemical properties of molecules, attributing to interactions with the transition state of individual molecules. Therefore, differences in the stability and reactivity as well as the molecular spectrum of the molecule is expected (23)(24)(25)(26).…”
Section: Methods Validation For Determination Of Asamentioning
confidence: 99%
“…The global chemical reactivity descriptors in (Table 1and Table 2) such as ionization potential (I), electron affinity (A), lowest unoccupied molecular orbital (ELUMO), highest occupied molecular orbital (EHOMO), and energy gap (Eg). electronegativity (χ), chemical potential (μ), molecular hardness (η), molecular softness (s), electrophilicity index (ω), Nucleofugality (ΔΕ ), and Electroofugality (ΔΕ ) in different types of solvents using equations (1-8) as shown below [27][28][29][30] . Where, I is ionization potential (I = -EHOMO) and A is electron affinity (A = -ELUMO).…”
Section: Global Reactivity Descriptors and Dipole Momentmentioning
confidence: 99%
“…In the last decades, the solvent's significant effect on the dipole moment has been reported in the literature. [48][49][50][51] It is found that the dipole moment is bigger in solution than in the gas phase. The dipole moment increases when going from lower to higher dielectric constant, i.e.…”
Section: Solvent Effectsmentioning
confidence: 99%